حساب تأثير القوى المتمركزة في سكونية نواقل محطات التوزيع المكشوفة - يوسف, يوسف (Latakia University Journal -Engineering Sciences Series, 2019)
تعتمد الطريقة التقليدية لحساب سكونية نواقل محطات التوزيع المكشوفة على الحل المستوي، وهي طريقة تقريبية تحتوي على أخطاء يظهر تأثيرها مع تعقيد البنية التصميمية لهذه المحطات، واستخدام عوازل طويلة ووجود نوازل (نواقل نازلة) من قضبان التجميع إلى الأجهزة الكهربائية والتي تعدّ وفقاً لهذه الطريقة قوى شاقولية. في هذا البحث سنقوم بإعداد النموذج الرياضي لحساب تأثير القوى المتمركزة في سكونية نواقل محطات التوزيع المكشوفة بالطريقة المتجهية، والتي يمكن عدّها خطوطاً مطلقة اللدونة. يتم حل النموذج الرياضي بالطرق العددية مع تحسين التقارب بطريقة وطسطن. انطلاقاً من النموذج الرياضي المقدّم تم إعداد برنامج بلغة (C++) يمكن استخدامه في التطبيقات الحسابية لحساب سكونية محطات التوزيع المكشوفة والقوى المناخية والمتمركزة المؤثرة في نواقلها وعوازلها، وحساب الشروط الابتدائية لديناميكية المحطة. بيّنت الدراسة أن حساب القوى المتمركزة بالطريقة الجديدة يخفض الأخطاء ما بين الطريقة الجديدة والطريقة التقريبية (المستوية) بحوالي 10%. The traditional method for the statistical calculation of the open distribution power station conductors, on the plane solution it is an approximate method which contains faults its effects appeared at the complicated infra-structural design, of that power station and long insulator using and descending carriers of the bus-bars to the electrical equipments, which could be considered as a perpendicular of (vertical) power. We used at our present work a mathematical model to calculate the central force effect on the statical transmission of the open power distribution station using the vector method as absolute plastic lines. Solving this mathematical model used the numerical method and the Whitiston-method. According to the new model, we adopted a C++ programme, for the arithmetical application to calculate the statistical open power station and the climatic forces and central effect power on the power station conductors and insulators, and, as well calculate the elementary condition of that power station dynamics. Our calculation of the central power with our new method will decrease the errors (or loss) between the new method and the approximate one by about 10%.